Meningkatkan Hasil Belajar IPAS Materi Metamorfosis Menggunakan Media Diorama pada Siswa Kelas III SD N Gudang Kopi 1 - Nabilah Desiana Putri; Agni Nuraeni; Elsa Elsa; Nova Aulia Syawal; Viqi Permadi Kusuma; Rana Gustian Nugraha (ENGGANG: Jurnal Pendidikan, Bahasa, Sastra, Seni, dan Budaya, 2026)
This research is motivated by students' low understanding of the abstract nature of metamorphosis, as well as the dominance of the lecture method in science learning, which results in low conceptual mastery. This study aims to improve science learning outcomes in metamorphosis through the use of dioramas for third-grade students at SDN Gudang Kopi 1. The method used was a qualitative approach with the Kemmis and McTaggart Classroom Action Research (CAR) model, implemented in two cycles. The research subjects consisted of 20 third-grade students. Data collection techniques included observation results, implementation of the CAR cycles, and documentation. The results showed a significant increase in the percentage of student learning completion, from 90% in the initial data to 98% in cycle I, and reaching 100% in cycle II. A comparison of pre-test and post-test scores also showed an increase in student abilities from the adequate to excellent category. Based on these findings, it can be concluded that the use of dioramas is effective in improving students' science learning outcomes because it can present abstract concepts in a more concrete, visual, and interactive way, as well as increasing student enthusiasm and active involvement in the learning process.